DE-MARGINALIZING SCIENCE IN THE ELEMENTARY CLASSROOM BY COACHING TEACHERS TO ADDRESS PERCEIVED DILEMMAS - Alissa Berg; Felicia M. Mensah (Arizona State University, 2014)
This study identified and explored the dilemmas experienced by three first-grade teachers in teaching elementary school science. The impact of coaching and teachers' career stages on how teachers reconciled their dilemmas was examined. Results of this comparative case study indicate that, when it came to teaching science, teachers perceived tensions between focusing instructional practice on science versus the other school subjects, tensions between their responsibility to teach science and their lack of a science background, and tensions between using their curriculum as a script, supplement, starting point, or not all. Participants reconciled their common dilemmas in different ways.  Extent of teaching experience; comfort level with teaching reading, writing, and mathematics; and the sense of accountability teachers felt to teach science were related to how effectively dilemmas were addressed. The amount of time spent with the science coach-researchers was tied to the amount of time science was taught and the extent to which teachers addressed dilemmas in reform-oriented ways.